ESMO Clinical Research Observatory (ECRO): improving the efficiency of clinical research through rationalisation of bureaucracy - Hendrik-Tobias Arkenau; Jean-Yves Douillard; Nicolas Penel; Teresa Amaral; Ahmad Awada; Emiliano Calvo; Viktor Gruenwald; Jose Luis Perez-Gracia; Ruth Vera; Martijn P Lolkema; Gyorgy Bodoky; Massimo Di Nicola; et al. (ESMO Open, 2020)
During the last years, there has been a dramatic increase in the administrative and bureaucratic burden associated with clinical research, which has clearly had an impact on its overall efficiency and on the activity of clinical investigators and research teams. Indeed, the supervision of the adherence of clinical research to Good Clinical Practice (GCP) guidelines and legal regulations is of the utmost importance. Yet, while such regulations have remained largely unchanged during recent years, the number of administrative tasks and their complexity have grown markedly, as supported by the results of a survey performed among 940 clinical investigators that we report in this manuscript. Therefore, many investigators believe that it has become necessary to undertake a rigorous analysis of the causes and consequences of this issue, and to create a conduit to channel the advice from experienced investigators regarding clinical research procedures, in order to improve them. Based on these premises, ESMO has launched the ESMO Clinical Research Observatory (ECRO), a task force that will analyse different aspects of clinical research. ECRO will aim to provide the views of ESMO on clinical research procedures based on the feedback from clinical investigators, under complete adherence to the Declaration of Helsinki, the GCP guidelines and any other applicable legal regulations, while at the same time showing profound respect for all the stakeholders involved in clinical research. This manuscript provides the background and rationale for the creation of ECRO, its planned activity and an analysis of the current administrative burden in clinical research with recommendations to rationalise it. Indeed, we expect that this effort shall lead to a relevant improvement in the care of patients and in the development of clinical research.